Managing Climate Risk in Water Supply Systems - Brown, Casey; Ward, Neil (IWA Publishing, 2013)
Water resources systems provide multiple services and, if managed properly, can contribute significantly to social well-being and economic growth. However, extreme or unexpected hydroclimatic conditions, such as droughts and floods, can adversely affect or even completely interrupt these services. This text seeks to provide knowledge, resources and techniques for water resources professionals to manage the risks and opportunities arising from hydroclimatic variability and change. Managing Climate Risk in Water Supply Systems provides materials and tools designed to empower technical professionals to better understand the key issues in water supply systems.